2019
DOI: 10.1002/aur.2116
|View full text |Cite
|
Sign up to set email alerts
|

The potential role of a retrotransposed gene and a long noncoding RNA in regulating an X‐linked chromatin gene (KDM5C): Novel epigenetic mechanism in autism

Abstract: A growing body of evidence supports the potential role of the circadian system and chromatin remodeling genes in autism. Considering the heterogeneity and gender discrepancy in autism, and the complex nature of the epigenetic landscape, identification of biologically relevant epigenetic factors requires reducing heterogeneity using proper subtyping. For this study, we used X chromosome inactivation (XCI) status in females with autism as an epigenetic marker for subtyping and examined the expression level of me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 63 publications
0
5
0
Order By: Relevance
“…There are also functional links between H3K9 methylation and DNA methylation in mammals 24 , 25 . SUV39H1/2 catalyzes the trimethylation of H3K9 and is necessary to maintain DNA methylation 26 , 27 . Dimethylation of H3K9 plays an equally important role in gene silencing and is catalyzed by distinct H3K9 methyltransferases, EHMT2 and EHMT2-like protein (EHMT1/GLP) 28 , 29 .…”
Section: Discussionmentioning
confidence: 99%
“…There are also functional links between H3K9 methylation and DNA methylation in mammals 24 , 25 . SUV39H1/2 catalyzes the trimethylation of H3K9 and is necessary to maintain DNA methylation 26 , 27 . Dimethylation of H3K9 plays an equally important role in gene silencing and is catalyzed by distinct H3K9 methyltransferases, EHMT2 and EHMT2-like protein (EHMT1/GLP) 28 , 29 .…”
Section: Discussionmentioning
confidence: 99%
“…Overexpression of X-linked genes may be a common mechanism underlying the development of psychiatric disorders in patients with these rare genetic diseases and in the general population of female psychiatric patients with XIST overexpression. Among the four X-linked escapee genes stated above, KDM5C is especially known to be related to psychiatric disorders including X-linked syndrome, autism, and depression (Ji et al, 2015 ; Vallianatos and Iwase, 2015 ; Talebizadeh et al, 2019 ). Indeed, female patients with MDD show increased expression of the XIST gene and KDM5C in lymphoblastoid cells (Ji et al, 2015 ).…”
Section: Epigenetic Mechanisms Of Sex-related Differences In Depressionmentioning
confidence: 99%
“…Indeed, female patients with MDD show increased expression of the XIST gene and KDM5C in lymphoblastoid cells (Ji et al, 2015 ). In addition, a recent clinical study has reported that, in blood samples, the expression levels of KDM5C-3’UTR-lncRNA isoform were different in autistic females with XCI skewness compared with controls (Talebizadeh et al, 2019 ). Intriguingly, a study of human postmortem brains supported overexpression of the XIST gene in female psychiatric patients (Ji et al, 2015 ).…”
Section: Epigenetic Mechanisms Of Sex-related Differences In Depressionmentioning
confidence: 99%
“…Previous study has also shown the importance of chromatin genes in ASD. Biologically relevant components of gene regulatory processes may collectively contribute to the etiology of ASD ( 10 ). However, no exact ASD causative genes have been identified, and the mechanisms linking them remain unclear.…”
Section: Introductionmentioning
confidence: 99%